The impact of the GST on mortgage pricing of Australian credit unions: An empirical analysis. Issue 1 (7th July 2014) - Liu, Benjamin; Huang, Allen; Freudenberg, Brett
Abstract : Purpose: – The purpose of this paper is to investigate the impact of the Goods and Services Tax (GST) on mortgage pricing and to measure the GST shifting ratio of Australian credit unions. Design/methodology/approach: – Using the proprietary data from 79 credit unions in Australia, we perform multivariate regression analysis on the effect of the GST on mortgage effective yield spreads and interest margins, respectively. We also introduce a model that is used to measure the GST shifting ratio. Findings: – We document that the introduction of the GST in July 2000 led to the substantial rise in mortgage costs charged by credit unions in the post-GST periods. Overall, the GST alone contributed to the increase of effective yield spreads and interest margin by 65.3 and 70.1 basis points, respectively. As measured by the GST-shifting ratio, credit unions passed more than twice of the GST rate. This suggests GST over-shifting, and it is generally consistent with tax over-shifting literature. Originality/value: – This is the first time the GST shifting ratio has been robustly measured with the use of multivariate models on mortgage costs.